P374 Can diffusion weighted MRI localise abnormalities acutely post-seizure?. Issue 9 (September 2017) - Tandoğan, Kamer; Toydemir, Hülya Ertaşoğlu; Yayla, Vildan; Resulova, Aygül; Demir, Elif; Yıldız, Omer; Inci, Ercan
Abstract : Objectives: We aimed to evaluate the electroencephalography (EEG) and diffusion weighted magnetic resonance (DWMR) findings obtained after a seizure in the acute period and to find out whether DWMR had any contribution to determine lateralization of epileptogenic activity. Methods: Consecutive 43 patients with a seizure admitted to emergency department between July 2016 and February 2017 were evaluated, retrospectively. Patients whose seizures occurred in the last three days were included in the study. Demographic and clinical features, EEG and radiologic findings of the patients were evaluated. Results: Mean age of total 43 patients was 48.12 ± 29.7 (18–80) years and 26 (60.5%) of them were female, 17 (39.5%) were male. Patients were divided into 3 groups regarding the classification of epileptic seizures; generalized ( n = 17), partial ( n = 23) and unclassified seizures ( n = 3). Ten patients (23.3%) had the diagnosis of epilepsy previously. Abnormalities in EEG and DWMR were detected in 55.8% and 16.3% of the patients, respectively. In addition, 6 patients of the 7 with MR abnormalities were from partial seizures and 1 patient from generalised seizures groups. Areas of diffusion restriction were consistent with the localization of EEG abnormalities in 4 out of 7 patients. Discussion: EEG is a valuable tool in supporting the diagnosis of epilepsy and classification of seizures. DWMR may be used in epilepsy patients to detect the areas that could be the cause of the epileptogenic activity in the post-ictal acute phase. Conclusions: Further studies with higher number of patients may investigate the relationship between EEG and DWMR abnormalities. Significance: This study may draw attention to relationship between neurophysiological and radiological findings in the acute period after a seizure.